Heritable genome editing with CRISPR/Cas9 in the silkworm, Bombyx mori. - Wei Wei; Huhu Xin; Bhaskar Roy; Junbiao Dai; Yungen Miao; Guanjun Gao (PLoS ONE, 2014)
We report the establishment of an efficient and heritable gene mutagenesis method in the silkworm Bombyx mori using modified type II clustered regularly interspaced short palindromic repeats (CRISPR) with an associated protein (Cas9) system. Using four loci Bm-ok, BmKMO, BmTH, and Bmtan as candidates, we proved that genome alterations at specific sites could be induced by direct microinjection of specific guide RNA and Cas9-mRNA into silkworm embryos. Mutation frequencies of 16.7-35.0% were observed in the injected generation, and DNA fragments deletions were also noted. Bm-ok mosaic mutants were used to test for mutant heritability due to the easily determined translucent epidermal phenotype of Bm-ok-disrupted cells. Two crossing strategies were used. In the first, injected Bm-ok moths were crossed with wild-type moths, and a 28.6% frequency of germline mutation transmission was observed. In the second strategy, two Bm-ok mosaic mutant moths were crossed with each other, and 93.6% of the offsprings appeared mutations in both alleles of Bm-ok gene (compound heterozygous). In summary, the CRISPR/Cas9 system can act as a highly specific and heritable gene-editing tool in Bombyx mori.